Early Repolarization Syndrome: Diagnostic and Therapeutic Approach - Bourier, Felix; Denis, Arnaud; Cheniti, Ghassen; Lam, Anna; Vlachos, Konstantinos; Takigawa, Masateru; Kitamura, Takeshi; Frontera, Antonio; Duchateau, Josselin; Pambrun, Thomas; Klotz, Nicolas; Derval, Nicolas; et al. (Frontiers in Cardiovascular Medicine, 2018)
An early repolarization pattern can be observed in 1% up to 13% of the overall population. Whereas this pattern was associated with a benign outcome for many years, several more recent studies demonstrated an association between early repolarization and sudden cardiac death, so-called early repolarization syndrome. In early repolarization syndrome patients, current imbalances between epi- and endocardial layers result in dispersion of de- and repolarization. As a consequence, J waves or ST segment elevations can be observed on these patients’ surface ECGs as manifestations of those current imbalances. Whereas an early repolarization pattern is relatively frequently found on surface ECGs in the overall population, the majority of individuals presenting with an early repolarization pattern will remain asymptomatic and the isolated presence of an early repolarization pattern does not require further intervention. The mismatch between frequently found early repolarization patterns in the overall population, low incidences of sudden cardiac deaths related to early repolarization syndrome, but fatal, grave consequences in affected patients remains a clinical challenge. More precise tools for risk stratification and identification of this minority of patients, who will experience events, remain a clinical need. This review summarizes the epidemiologic, pathophysiologic and diagnostic background and presents therapeutic options of early repolarization syndrome.